Efficacy of chitosan-coated textile waste biochar applied to Cd-polluted soil for reducing Cd mobility in soil and its distribution in moringa (Moringa oleifera L.). (15th April 2021) - Zubair, Muhammad; Adnan Ramzani, Pia Muhammad; Rasool, Bilal; Khan, Muhammad Asaf; ur-Rahman, Mahmood; Akhtar, Imran; Turan, Veysel; Tauqeer, Haﬁz Muhammad; Farhad, Muniba; Khan, Shahbaz Ali; Iqbal, Javed; Iqbal, Muhammad
Abstract: Soil pollution with Cd has promoted serious concerns for medicinal plant quality. Amending Cd-polluted soils with textile waste biochar (TWB) coated with natural polymers can lower Cd bioavailability in them and reduce associated environmental and human health risks. In this study, we explored the impacts of solely applied TWB, chitosan (CH), their mix (TWB + CH) and TWB coated with CH (TBC) in Cd-polluted soil on Cd distribution in moringa ( Moringa oleifera L.) shoots and roots as well as plant-available Cd in soil. Moreover, amendments effects on plant growth, dietary quality, and antioxidative defense responses were also assessed. Results revealed that the addition of TWB, CH, and TWB + CH in Cd-polluted soil reduced Cd distribution in shoots (56%, 66%, and 63%), roots (41%, 48%, and 45%), and plant-available Cd in soil (38%, 52%, and 49%), compared to control. Interestingly, the TBC showed significantly the topmost response for reducing Cd concentrations in shoots, roots, and soil by 73%, 54%, and 58%, respectively, relative to control. Moreover, amending Cd-polluted soil with TWB, CH, and TWB + CH depicted significantly better effects on plant growth, dietary quality, and activities of soil enzymes but the topmost response was observed with TBC treatment. Compared with control, TBC improved plant growth parameters: shoot length (81%), root length (90%), shoot fresh weight (60%), root fresh weight (76%), shoot dry weight (75%), root dry weight (68%) contents of chlorophyll-a (42%) and chlorophyll-b (74%), and soil enzyme activities: urease (130%), catalase (138%), protease (71%), cellobiohydrolase (45%), acid phosphatase (34%), peroxidase (60%), β-glucosidase (152%), chitinase (62%), and phosphomonoesterase (139%). Furthermore, TBC treatment arrested Cd-induced oxidative stress via escalating the activities of antioxidant enzymes as well as improved moringa dietary parameters (protein, tannins, lipids, alkaloids, saponins, terpenoids, flavonoids, and tocopherols contents). Such findings suggest that the TBC has an immense perspective to remediate Cd-polluted soils and prevent human health risks associated with Cd exposure through the diet. Graphical abstract: Image 1 Highlights: Cadmium polluted soil was amended with TWB, CH, TWB + CH, and TBC for Cd immobilization. TBC reduced Cd in moringa shoots (73%) and roots (54%) by altered Cd fractions. Amending with TBC improved moringa capacity to manage Cd-induced oxidative injury. Moringa growth, biochemical, and nutritional prestige was the highest with TBC. TBC led the premier improvement in the enzymatic activities of Cd-polluted soil.